2018
DOI: 10.1111/acem.13420
|View full text |Cite
|
Sign up to set email alerts
|

Physician Age and Performance on the American Board of Emergency Medicine ConCert Examination

Abstract: After physician characteristics were controlled for, there was an association between advancing age and declining performance on the ABEM ConCert examination. This information may be important to the individual physician to develop targeted competency assessment and professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We found that increased physician age was associated with increased patient mortality. Lending credence to our model is that our finding is concordant with many studies that have demonstrated negative associations of age with educational and patient-relevant outcomes 3 35 36. Based on our proposed mechanism, it is plausible that increased age, and in particular time from completion of medical training, may make staying current in knowledge and practice more challenging 37 38.…”
Section: Discussionsupporting
confidence: 85%
“…We found that increased physician age was associated with increased patient mortality. Lending credence to our model is that our finding is concordant with many studies that have demonstrated negative associations of age with educational and patient-relevant outcomes 3 35 36. Based on our proposed mechanism, it is plausible that increased age, and in particular time from completion of medical training, may make staying current in knowledge and practice more challenging 37 38.…”
Section: Discussionsupporting
confidence: 85%
“…Personal Characteristics, such as high educational attainment and age-related maturity, were also highlighted by patients. Age-related expectations, which link age, experience and skill levels, are deeply rooted in the Chinese culture, even though age and performance are not necessarily positively correlated [ 62 , 63 ]. According to Chinese physician recruitment rules, doctors with lower education and experience are more likely to work in primary care institutions than hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Since skills naturally tend to decay over time without actions to prevent decline, 1 determinations about professional competency made years earlier (e.g., in residency training or by initial specialty certification) have diminishing predictive association with evolving expectations for professional competency over time. 22 Certification exists to set the current standard for specialty competencies, and continuing certification must determine whether each certified physician is adequately maintaining those skills and abilities through a rigorous assessment program. 23 Doing so allows the specialty boards to reassure the public, including patients and family members, about their physicians’ abilities to provide safe and effective care.…”
Section: What Is the Role And Value Of Continuing Certification Over ...mentioning
confidence: 99%